Refuse-derived plastic from waste expanded polystyrene and used deep-fried oil - Noor Aishatun, Majid (Universiti Malaysia Perlis, 2011)
A refuse-derived plastic was produced by mixing waste Expanded Polystyrene (EPS) in solution with used deep-fried oil (UDFO). A measured amount of methyl ethyl ketone peroxide (MEKPO) was added as a reaction initiator and cobalt-naphthenate as a promoter. Investigation of solubility test of EPS in MEK solvent indicates that 5 g waste and EPS 10 g MEK were found to be an effective mixture to make the best formulation in making refuse-derived plastic. Experiments on preparation of refuse-derived plastics with different amount of used deep-fried oil and Polystyrene in MEK solution indicates that 15 wt. % of UDFO cooperated well with waste EPS and resulted the highest tensile strength and maximum stress (flexural strength) 3.579 MPa and 6.520 MPa. The morphology and performance characteristic of the prepared waste expanded polystyrene (EPS) based plastic filled with 15 wt. % used deep-fried oil (UDFO) and 15 wt. % fresh oil (FO) were determined and compared. The tests showed that the prepared refuse-derived plastic has some advantages such as excellent tensile strength, elongation at break, modulus of elasticity and flexural strength compared with waste expanded polystyrene (EPS) based plastic filled with 15 wt. % with fresh oil (FO).